(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Today, issues of interethnic harmony and cultural tolerance are becoming increasingly relevant on a global scale. Ensuring mutual respect, peace and harmony between different nationalities and ethnic groups is not only the basis of social stability, but also an important factor in national development. In this regard, the need arises to introduce effective pedagogical approaches and technologies aimed at the formation and development of interethnic harmony in the educational system. In particular, artpedagogical technologies occupy a special place in the education of interethnic harmony. These technologies expand the emotional and creative possibilities of students through the means of art, encouraging them to deeper understand and respect the culture of others.